1991
DOI: 10.1520/jfs13019j
|View full text |Cite
|
Sign up to set email alerts
|

Threatening and Otherwise Inappropriate Letters to Hollywood Celebrities

Abstract: In this paper, the authors examine the characteristics of threatening and otherwise inappropriate letters sent to Hollywood celebrities. Such communications, known colloquially as “nut mail,” “hate mail,” obscene letters, and threat letters, are received by the famous in enormous volume. We studied approximately 1800 such letters to entertainment celebrities from 214 subjects, who averaged 8 letters apiece. We quote excerpts from these letters, describe objects enclosed with them, and provide quantitative data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
4
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 4 publications
9
97
4
1
Order By: Relevance
“…There is a modest literature that empirically examines threats (Calhoun, 1998;Dietz et al, 1991aDietz et al, , 1991bMeloy, 2001;Scalora, Baumgartner, & Plank, 2003). One of the few systematic studies of psychiatric assessment after uttering a homicidal threat reported nearly half to be psychotic and most of the rest personality disordered (MacDonald, 1968).…”
Section: The Assessment Processmentioning
confidence: 99%
“…There is a modest literature that empirically examines threats (Calhoun, 1998;Dietz et al, 1991aDietz et al, , 1991bMeloy, 2001;Scalora, Baumgartner, & Plank, 2003). One of the few systematic studies of psychiatric assessment after uttering a homicidal threat reported nearly half to be psychotic and most of the rest personality disordered (MacDonald, 1968).…”
Section: The Assessment Processmentioning
confidence: 99%
“…The scientific literature presents contradictory views on the emotions caused by threat. Psychological consequences of threat are often referred to the emotional sphere: anxiety, fear, and depression of a reader (Dietz et al, 1991). Intensive manifestation of emotions influences adequate perception of the image of the threat.…”
Section: Problem Statementmentioning
confidence: 99%
“…As reported in [2], six studies have been carried out to date on abnormal communication and approach to prominent people: one on the British royal family [18], two on Hollywood celebrities [19,20], and three on the U.S. Congress [21,22,23]. The studies relate the occurrence of problematic approaches to factors such as mental illness, threatening or antagonistic communication, requests for help, multiple means of communication, and multiple contacts and targets.…”
Section: Existing Work On Abnormal Communications and Approachesmentioning
confidence: 99%
“…Use of insights of existing studies on abnormal communications and approaches [18][19][20][21][22][23] to tune the information extraction and content analysis capabilities available in the Frames in Action platform to the protective intelligent domain. The code books (list of factors and their explanation) developed in these studies (e.g.…”
Section: Using the Frames In Action Platform For Protective Intelligencementioning
confidence: 99%